“It makes a world of difference”:A photo-elicitation study of resigning EFL teachers’ resilience and well-being - Keshmirshekan , Mohammad Hossein; Hashemi, Mohammad Reza; Karimi, Mohammad Nabi (Assessment and Practice in Educational Sciences, 2025)
Recent developments in arts-based research have highlighted the potential of visual methodologies to deepen educators’ understanding of the personal and professional dynamics shaping their teaching practices. Despite their increasing application across educational disciplines, such approaches remain underutilized in second language teacher education research. This mixed methods study, employing an explanatory sequential design, investigates the impact of photo-elicitation on the well-being and resilience of ten Iranian EFL teachers who had decided to resign from their positions in private language institutes. The participants, four males and six females with 9 to 14 years of teaching experience, were purposively selected to explore how arts-based engagement might reframe their professional narratives. Quantitative findings indicated statistically significant improvements in participants' post-course levels of well-being and resilience. Complementary qualitative analysis revealed that participation in the photo-elicitation workshop fostered enhanced self-regulation, greater insight into resilience mechanisms, emotional articulation, narrative re-construction, and holistic self-appraisal. These findings underscore the transformative potential of arts-based visual methods in facilitating emotional insight and professional renewal among language teachers. The study offers implications for teacher education, suggesting that integrating photo-elicitation can be a powerful pedagogical tool to support teacher well-being and resilience.